2011
DOI: 10.1016/j.jpeds.2011.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guidelines for Managing Patients with 22q11.2 Deletion Syndrome

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
656
3
57

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 539 publications
(751 citation statements)
references
References 42 publications
13
656
3
57
Order By: Relevance
“…Patients are diagnosed with 22q11DS at different stages in their lives and early recognition can significantly change the medical management, follow‐up and genetic counseling, which are useful for the patient, family, and clinicians (Bassett et al, 2011; Kapadia & Bassett, 2008). Across the included studies, many parents reported feelings of powerlessness and frustration as a result of having to wait years for a diagnosis for their child (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012), which resulted in increased uncertainty about the child's future (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Martin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are diagnosed with 22q11DS at different stages in their lives and early recognition can significantly change the medical management, follow‐up and genetic counseling, which are useful for the patient, family, and clinicians (Bassett et al, 2011; Kapadia & Bassett, 2008). Across the included studies, many parents reported feelings of powerlessness and frustration as a result of having to wait years for a diagnosis for their child (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012), which resulted in increased uncertainty about the child's future (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Martin et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, patient psychosocial perspectives were limited; limited findings highlighted patients’ desires to obtain independence, challenges to achieving individualism, and transitioning into adulthood. Reasons for this may include limitations in patients’ social functioning disproportionate to their capabilities in other aspects of daily living (Angkustsiri et al, 2012; Bassett et al, 2011; Butcher et al, 2012; Ho et al, 2012), difficulty maintaining social relationships (Abery & Fahnestock, 1994; May & Simpson, 2003), and having small social circles (Amando, 1993; Knox & Hickson, 2001). However, these patterns were not necessarily found for all 22q11DS patients included in this review: a number of female patients in (Phillips et al, 2017) express strong desires to marry and become good parents.…”
Section: Discussionmentioning
confidence: 99%
“…The 22q11.2DS is the most common microdeletion syndrome and is characterized by broad phenotypic heterogeneity including multiple congenital anomalies, such as tetralogy of Fallot and cleft palate (Bassett et al, 2011; McDonald‐McGinn et al, 2015). Due to these conditions, often requiring urgent medical/surgical attention, possible orthopedic features tend to be overshadowed, as shown by the fact that there are no studies on the treatment of orthopedic manifestations within 22q11.2DS (Homans et al, 2017; Homans et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is just a small portion of all the associated anomalies within 22q11.2DS (Bassett et al, 2011; McDonald‐McGinn et al, 2015). Stone et al performed a long‐term study on the associated anomalies found in patients with presumed idiopathic club foot (Stone et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation